Ethanol production via simultaneous saccharification and fermentation of sodium hydroxide treated corn stover using Phanerochaete chrysosporium and Gloeophyllum trabeum - Vincent, M.; Pometto III, A.L.; Leeuwen, J.V. (Elsevieer, 2014)
Ethanol was produced via the simultaneous saccharification and fermentation (SSF) of dilute sodium hydroxide treated corn stover. Saccharification was achieved by cultivating either Phanerochaete chrysosporium or Gloeophyllum trabeum on the treated stover, and fermentation was then performed by using either Saccharomyces cerevisiae or Escherichia coli K011. Ethanol production was highest on day 3 for the combination of G. trabeum and E. coli K011 at 6.68 g/100 g stover, followed by the combination of P. chrysosporium and E. coli K011 at 5.00 g/100 g stover. SSF with S. cerevisiae had lower ethanol yields, ranging between 2.88 g/100 g stover at day 3 (P. chrysosporium treated stover) and 3.09 g/100 g stover at day 4 (G. trabeum treated stover). The results indicated that mild alkaline pretreatment coupled with fungal saccharification offers a promising bioprocess for ethanol production from corn stover without the addition of commercial enzymes.